Ketahanan Rantai Pasok API Global: Ketergantungan terhadap Tiongkok dan India serta Strategi Mitigasi - Nurfiani, Suharti; S, Delseusy Ana; Y, Fransiska Valeria; Putri, Artika (Program Studi Farmasi Sekolah Tinggi Ilmu Kesehatan Sambas, 2025)
The resilience of the global Active Pharmaceutical Ingredients (API) supply chain has become a strategic issue in public health systems, especially due to the high dependence on two major suppliers: China and India. This reliance poses significant risks in the event of production disruptions, geopolitical conflicts, or restrictive export policies. This study aims to analyze the core challenges in the global API supply chain and identify mitigation strategies that can be applied by developing countries such as Indonesia. A descriptive qualitative method was used through a literature review of secondary data, including national journals, government policy documents, and reports from global health organizations such as WHO and WTO. The findings show that dependence on China and India significantly affects the availability and pricing of medicines and disrupts the continuity of national pharmaceutical production. Three main mitigation strategies are identified: diversification of API sources, strengthening of domestic API manufacturing through incentives and industrial zones, and adoption of digital technologies to improve supply chain visibility. In conclusion, building API supply chain resilience requires an integrated approach involving government support, industry collaboration, and international cooperation. This study emphasizes the urgency for pharmaceutical system transformation to become more self-reliant and responsive to global challenges.